Pengajuan Kasasi Tindak Pidana Ringan (Studi Relaas Pemberitahuan Putusan Banding Nomor 164/Pid/2019/PT Smr) - Norhani, Ulfah; Zairani Lisi, Ivan; Gusta Andini, Orin (Jurnal Risalah Hukum, 2022)
Cassation Law is the right of the defendant or public prosecutor not to accept the court's decision. Cases categorized as minor crimes are cases where the threat of a criminal verdict is a maximum of 3 months of confinement/imprisonment and a fine, one of which is a criminal act of using land without permission. The purpose of this study is to review and analyze, first, the legal arrangements for filing appeals according to SEMA No. 8 of 2011 against cases of minor criminal acts of using land without permission Decision Number 164 / Pid / 2019 / PT Smr and legal considerations of the Bailiff of the Samarinda District Court in issuing a notice of appeal decision No. 164 / Pid / 2019 / PT Smr which explains that the defendant can apply for cassation. The results showed that the legal arrangement for filing an appeal according to SEMA No. 8 of 2011 against cases of minor criminal acts of using land without permission Decision Number 164 / Pid / 2019 / PT Smr is a case that is not eligible to be appealed because the criminal verdict falls on qualifications that are threatened with imprisonment under 1 (one) year. Legal considerations for the issuance of a notice of appeal decision No. 164/Pid/2019/PT Smr, which explains that the defendant can apply for an appeal based on the Bailiff being obliged to convey the Right of a Defendant because the defendant has the right to file an appeal and in Article 205 of the Criminal Procedure Code regarding the examination of minor crimes there is no specific mention of the prohibition of filing appeals.